Anti-Oedipus: Capitalism and Schizophrenia - Deleuze, Gilles 1925-1995; Guattari, Félix 1930-1992 (Minneapolis University of Minnesota Press, 1983)
The authors set forth a theory that "Western society's innate herd instinct has allowed the government, the media, and even the principles of economics to take advantage of each person's unwillingness to be cut off from the group" and that "those who suffer from mental disorders my not be insane, but could be individuals in the purest sense."--Publisher's description.